Ocular manifestations as first signs of systemic T cell lymphoma in two cases - Xiao Zhang; Xin-Shu Liu; Chan Zhao; Ya-Min Lai; Mei-Fen Zhang (BMC Ophthalmology, 2017)
Abstract Background Intraocular involvement of systemic T-cell lymphomas are uncommon and have been broadly regarded as markers of poor prognosis. We reported two cases of uveitis patients finally diagnosed as systemic T cell lymphoma. Case presentation Case one is a 19-year-old female presented with fever and liver dysfunction, and was diagnosed as EBV-associated chronic active hepatitis. Fourteen months later, she suffered from recurrent granulomatous anterior uveitis in both eyes, which failed to respond to steroid and immunosuppressant therapy. A mass on the left side of pharynx was found and the final diagnosis was pharynx T cell non-Hodgkin’s lymphoma. After 13 cycles of chemotherapy, her systematic symptoms and uveitis relieved a lot, and eye condition is stable after cataract surgery. Case two is a 37-year-old male complaining bilateral blurred vision and recurrent abdominal pain. Panuveitis was diagnosed and anterior inflammation did not release after topical steroid. During the following days, the patient complained intermittent abdominal pain and fever, with rapidly progressive bilateral visual decrease. Final diagnosis was gallbladder type II enteropathy-associated T-cell lymphoma. The patient died of multiple organ failure 4 days after operation that was only 26 days after presenting to our hospital. Conclusions Ocular manifestations as first signs of systemic T cell lymphoma were rare. Diagnosis of lymphoma has to be suspected when patients have systemic manifestations including fever, fatigue, abdominal pain, EBV-associated liver disease, et al., and uveitis fails to respond to steroid therapy.